Synthesis of a Tetraepoxy Nanobelt and Its Reductive Aromatization Attempts - Han, Yi; Dong, Shaoqiang; Liau, Yuan Cheng; Chi, Chunyan (Organic Materials, 2020)
Hydrocarbon nanobelts have recently attracted tremendous interest. Herein, we report our recent progress towards the synthesis of a newly designed hydrocarbon nanobelt tetrabenzo[10]cyclacene, which can be regarded as a sidewall fragment of the (10,0) carbon nanotube. The structures of both key intermediates — “U”-shape diepoxy building block and tetraepoxy nanobelt — were confirmed by single-crystal X-ray diffraction. Our preliminary reductive aromatization reactions revealed that a tetrahydrogenated species instead of tetrabenzo[10]cyclacene was formed during this process. Computational results further revealed that hydrogenation can lead to significant strain release of the backbone structure of tetrabenzo[10]cyclacene, which may attribute to the absence of the target compound during the reductive aromatization.
Keywords: hydrocarbon nanobelts; reductive aromatization; hydrogenation; strain